PERILAKU DAN PENETAPAN HARGA INDUSTRI RAFTING DI SUNGAI TELAGA WAJA BALI - Widanta, A.A. Bagus Putu; Sukadana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
A market that has only two to a few strong players in the market is called an oligopoly market. The players in the oligopoly market are highly dependent on each other. Several types of businesses in Bali have an oligopoly market structure with a limited number of actors and have the power to set the bid price. One of them is white water rafting on the Telaga Waja river which consists of several companies and can be categorized into an oligopoly market structure. In a tight oligopoly market structure, the leading company acts arbitrarily in setting prices. This study wants to find out whether the net price for rafting is rational and above the BEP price and wants to see the behavior of companies in price and non-price competition in the Telaga Waja River rafting business, Karangasem Bali. The results showed that there was no agreement in determining the net price in the Telaga Waja rafting industry. They compete on non-price by holding massive promotions and differentiating rafting products which results in higher costs incurred and reduces profits. The results of the study provide an overview to the relevant agencies, rafting entrepreneurs and water tourism associations in formulating the most appropriate price and promotion packages for the rafting industry to face competition and maintain the sustainability of the rafting business on the Telaga Waja River, Karangasem Regency, Bali.